2011
DOI: 10.1074/jbc.m111.289983
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Stimulation of Recombinant DNA Polymerase γ and Mitochondrial DNA (mtDNA) Helicase by Variants of Mitochondrial Single-stranded DNA-binding Protein (mtSSB) Correlates with Defects in mtDNA Replication in Animal Cells

Abstract: Background: Mitochondrial single-stranded DNA-binding protein (mtSSB) coordinates the functions of the mitochondrial DNA (mtDNA) polymerase and helicase. Results: mtSSB variants are defective in stimulating mtDNA polymerase and helicase. Conclusion: mtSSB uses distinct structural elements to interact with mtDNA polymerase and helicase. Significance: Novel insights are presented into the mechanism of mtDNA replication and the role of mtSSB in human diseases involving mtDNA depletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 43 publications
5
71
0
Order By: Relevance
“…Although these alterations were not CS-specific, in CS cells the depletion of Twinkle and mtSSB cumulated with the imbalance of the POLG1/POLG2 complex, possibly enhancing the DNA replication defect in these cells. Interestingly, these data suggest that mtSSB is far less needed for mtDNA maintenance than hitherto believed (46,47), and this point may need to be developed in future studies. We showed that mtDNA maintenance was altered in CS cells: mtDNA content was either dramatically reduced or increased in these cells, and affected the 7S/mtDNA ratio.…”
Section: Discussionmentioning
confidence: 82%
“…Although these alterations were not CS-specific, in CS cells the depletion of Twinkle and mtSSB cumulated with the imbalance of the POLG1/POLG2 complex, possibly enhancing the DNA replication defect in these cells. Interestingly, these data suggest that mtSSB is far less needed for mtDNA maintenance than hitherto believed (46,47), and this point may need to be developed in future studies. We showed that mtDNA maintenance was altered in CS cells: mtDNA content was either dramatically reduced or increased in these cells, and affected the 7S/mtDNA ratio.…”
Section: Discussionmentioning
confidence: 82%
“…Mutagenesis of DmmtSSB-Mutagenesis was performed in the pMt/Hy vector to generate the Drosophila mtSSB loop 2,3 variant as described previously (7). The open reading frame was amplified by PCR with the forward 5Ј-ATACATATGGCAAC-AACAACAACGGCAGCGGCT-3Ј and reverse 5Ј-TATAGA-TCTTTAGTTGTTGGCATCACGGAAAAACAA-3Ј primers.…”
Section: Methodsmentioning
confidence: 99%
“…It lacks the loop 2,3 structure and contains an ϳ60-amino acid C-terminal extension that is implicated in interactions with its protein partners. Despite these differences, EcSSB is capable of stimulating both HsPol ␥ and DmPol ␥ (7,22). On the other hand, HsmtSSB is not able to substitute for EcSSB in vivo (even in the presence of the C terminus of EcSSB) (28).…”
Section: Dna Polymerization Activity Of Pol ␥ Depends On the Molarmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined further the stimulation of dsDNA unwinding by human mtDNA helicase by wild-type mtSSB and several variant forms, targeting amino acid residues that are conserved among mtSSBs but not present in E. coli SSB by alanine-substitution and deletion mutagenesis (Oliveira & Kaguni, 2011). Whereas maximal stimulation of human mtDNA helicase can be achieved both by human mtSSB and non-cognate SSBs including D. melanogaster mtSSB and E. coli SSB, several of the human variants exhibited substantially reduced stimulation.…”
Section: Structure and Catalytic Activitymentioning
confidence: 99%